2011
DOI: 10.1007/s10457-011-9424-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on the growth of tropical agroforestry tree seedlings

Abstract: Several studies have been conducted on the response of crops to greater concentrations of atmospheric CO 2 (CO 2 fertilization) as a result of climate change, but only few studies have evaluated this effect on multipurpose agroforestry tree species in tropical environments. The objectives of this study were to quantify differences in growth parameters and in leaf carbon (C) and nitrogen (N) concentrations of Cedrela odorata L. and Gliricidia sepium (Jacq.) Walp. seedlings under current ambient temperature (32°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…2B, ontological effects during seedling development must be considered. Nevertheless, a significant increase in the shoot:root biomass ratio and an increase in internode length within stems (data not shown) are consistent with previous observations of increased tree height at higher growth temperatures (Way and Oren, 2010; Esmail and Oelbermann, 2011). Dependent upon whether this is caused by changes in cell elongation and/or the promotion of apical meristem activity, it is likely to have profound implications upon mechanical stability, and competitive interaction of stems during growth.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2B, ontological effects during seedling development must be considered. Nevertheless, a significant increase in the shoot:root biomass ratio and an increase in internode length within stems (data not shown) are consistent with previous observations of increased tree height at higher growth temperatures (Way and Oren, 2010; Esmail and Oelbermann, 2011). Dependent upon whether this is caused by changes in cell elongation and/or the promotion of apical meristem activity, it is likely to have profound implications upon mechanical stability, and competitive interaction of stems during growth.…”
Section: Discussionsupporting
confidence: 92%
“…While the lack of data on tropical trees is recognized as a limitation in such an analysis (Lin et al , 2010; Way and Oren, 2010), there has yet to be substantial improvement in the number (or range) of tropical species for which the fundamental response to elevated temperature is known. In the small number of empirical studies that have sought to elucidate fundamental thermal niches of tropical tree species, maximum growth has often been found under the highest temperature regime tested (Herwitz, 1993; Cunningham and Read, 2003; Allen and Vu, 2009; Esmail and Oelbermann, 2011; Cheesman and Winter, 2013). In these cases, the thermal optimum for growth was found to be higher than that predicted by either climatic home range or photosynthetic thermal optimum (Cunningham and Read, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, these impacts are reduced in seedlings infected with Rhizobium tropici (root nodule bacteria) (Pereyra et al, 2015). On the contrary, we also have LoE2a strength evidence, which suggest that climate change, manifested through a combined effect of increased atmospheric temperatures and elevated CO 2 , could benefit trees species (Cedrela odorata and Gliricidia sepium) in terms of faster growth (Esmail and Oelbermann, 2011). However, the increased growth rate comes with a trade-off: the reduction of leaf nutrient value.…”
Section: The Impacts Of Climate Change On Tafs Treesmentioning
confidence: 65%
“…However, other evidence has indicated that tree growth increases by climate change are not related to CO2 fertilization, but to temperature increase, stronger drought resistance, or nutrient fertilization (Bertini et al, 2011;Ise and Moorcroft, 2010;Magalhães et al, 2014;Poulter et al, 2013;Salzer et al, 2009). Moreover, some experiments on growth under elevated CO2 concentration have shown no effect (Bader et al, 2013;Booth, 2013), or even growth decrease (Esmail and Oelbermann, 2011). In fact, it has been argued that the generalized belief on CO2 fertilization effects could even be due to sampling bias (Brienen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%